Functional role of putative critical residues in Mycobacterium tuberculosis RNase P protein. (September 2016) - Singh, Alla; Ubaid-ullah, Shah; Batra, Janendra K.
Abstract: RNase P is involved in processing the 5⿲ end of pre-tRNA molecules. Bacterial RNase P contains a catalytic RNA subunit and a protein subunit. In this study, we have analyzed the residues in RNase P protein of M. tuberculosis that differ from the residues generally conserved in other bacterial RNase Ps. The residues investigated in the current study include the unique residues, Val27, Ala70, Arg72, Ala77, and Asp124, and also Phe23 and Arg93 which have been found to be important in the function of RNase P protein components of other bacteria. The selected residues were individually mutated either to those present in other bacterial RNase P protein components at respective positions or in some cases to alanine. The wild type and mutant M. tuberculosis RNase P proteins were expressed in E. coli, purified, used to reconstitute holoenzymes with wild type RNA component in vitro, and functionally characterized. The Phe23Ala and Arg93Ala mutants showed very poor catalytic activity when reconstituted with the RNA component. The catalytic activity of holoenzyme with Val27Phe, Ala70Lys, Arg72Leu and Arg72Ala was also significantly reduced, whereas with Ala77Phe and Asp124Ser the activity of holoenzyme was similar to that with the wild type protein. Although the mutants did not suffer from any binding defects, Val27Phe, Ala70Lys, Arg72Ala and Asp124Ser were less tolerant towards higher temperatures as compared to the wild type protein. The Km of Val27Phe, Ala70Lys, Arg72Ala and Ala77Phe were >2-fold higher than that of the wild type, indicating the substituted residues to be involved in substrate interaction. The study demonstrates that residues Phe23, Val27 and Ala70 are involved in substrate interaction, while Arg72 and Arg93 interact with other residues within the protein to provide it a functional conformation.